REVIEW ON THE BOOK “AN EXPERT ESTIMATION OF PSYCHIC DISABILITIES IN PERSONS EXPOSURED TO ELEVATED LEVEL OF RADIATION: THE GUIDE FOR GENERAL PARTITIONS AND PSYCHOLOGISTS ” (FO “SSMC AND SP AFTER V.P. SERBSKY”) - G. V. Arkhangelskaya; V. M. Shubik V.M (Радиационная гигиена)
.